A Study on Automatic Passenger Mover Envelope Gauge. (September 2016) - ji, Y; Ren, L; Song, Y
Abstract: Based on structural feature of running gear of APM and referring to research achievement, the method of calculating APM envelope gauge is discussed and an example is illustrated. A reference for drawing up the standard of APM envelope gauge is provided.